THE EFFECTIVENESS OF INTERACTIVE ANIMATION MULTIMEDIA IN INCREASING THE LEARNING MOTIVATION OF GRADE V STUDENTS - Tatik Sugiwati Tatik; Ardi Samudra Rochmattulloh Ardi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to find out how much influence interactive animation multimedia has in increasing the learning motivation of class V students in school cluster 05 Banyuwangi District, which consists of SDN Tamanbaru, SDN Kebalenan, SDN Sobo, SDN Sumberrejo, SDN Kertosari 1, SDN Kertosari 2 dan SDN Model. Sampling was conducted using random sampling with a shaking system. So, the experimental class and the control class were chosen. The results of the study show that: 1) The validity of the learning motivation questionnaire is very valid r calculate > r table; 2) The reliability of the X variable is 0.926, and the Y is 0.845 Excellent and Good Reliable Categories; 3) Homogeneous; 4) Normally distributed; 5) there is a linear relationship between the independent variable and the bound variable; 6) There is a positive influence between the use of interactive animation multimedia on learning motivation. So, interactive animation multimedia has an effective impact on learning motivation by 71.3%.